Nutritional evaluation of dried tomato seeds - Persia, M.E.; Parsons, C.M.; Schang, M.; Azcona, Jorge Oscar (Oxford Academic Press, 2019)
Two samples of tomato seeds, a by-product of the tomato canning industry were evaluated to determine proximate analysis, amino acid content, and digestibility, TMEn, and protein efficiency ratio. Tomato seeds were also used to replace corn and soybean meal (SBM) in a chick diet on an equal true amino acid digestibility and TMEn basis. Tomato seeds were found to contain 8.5% moisture, 25% CP, 20.0% fat, 3.1% ash, 35.1% total dietary fiber, 0.12% Ca, 0.58% P, and 3,204 kcal/kg of TMEn. The total amounts of methionine, cystine, and lysine in the tomato seeds were 0.39, 0.40, and 1.34%, respectively, and their true digestibility coefficients, determined in cecectomized roosters, were 75, 70, and 54%, respectively. The protein efficiency ratio (weight gain per unit of protein intake) value when fed to chicks at 9% CP was 2.5 compared to 3.6 for SBM (P < or = 0.05). When corn-SBM diets were formulated on an equal true amino acid digestibility and TMEn basis, up to 15% tomato seeds could replace corn and SBM without any adverse affects on chick weight gain, feed intake, or gain:feed ratio from 8 to 21 d posthatch. Tomato seeds at any level in the diet did not significantly affect skin pigmentation. Although the protein quality of tomato seeds may not be as high as SBM, tomato seeds do contain substantial amounts of digestible amino acids and TMEn. When formulating diets on a true digestible amino acid and TMEn basis, tomato seeds can be supplemented into chick rations at up to 15% without any adverse affects on growth performance.